Outcomes after Trifocal Femoral Fractures - Michelle Griffin; Alastair G. Dick; Shamim Umarji (Case Reports in Surgery)
Trifocal femur fractures are those of the femoral neck, diaphysis, and distal femur. These high-energy injuries predominantly occur in young people with the potential for long-term complications and disability. We present the cases of two men who were treated with proximal dynamic hip screws and distal periarticular locking plates to effectively manage trifocal femur fractures. Our cases have shown union at 2 years with good functional outcomes without the need for reintervention. We provide evidence for a successful surgical treatment option for these rare and complex injuries.